"Место, где Бог по‐особому прикоснулся к земле": интернациональность и интеркультурность Междугорья - Belaj, Marijana (Array, 2014)
After the work by the Dutch anthropologist Mart Bax, Medjugorje gained an academic reputation of a showcase for a pilgrimage space with religious, ethnic and political conflicts. From the very beginning of its pilgrimage history, Medjugorje as a sacred place attracted believers of various religious affiliations. The intention of this paper is to open up a different perspective in contrast to one proposed by Bax, namely, a perspective of international and intercultural communication through the shaping of Medjugorje pilgrimage. By analyzing primarily narrative expressions, but also embodied experiences and material objects, the paper sketches situations and manifestations of such interaction and communication. At the same time, it points to the obstacles in the processes that have emerged from the construction and interpretation of cultural differences. The paper concludes with an attempt to show that Medjugorje may be seen as an example of interculturality, unless religion and identity are not approached as something given or as a kind of a ghetto.